Crowdsourcing-Based Application to Know Road Conditions in Malang City - Syahdan Hidayat; Setiabudi Sakaria; Bagus Kristomoyo Kristanto (J-INTECH ( Journal of Information and Technology), 2021)
The city of Malang as a city of education and tourism has seen an increase in the number of vehicles that can cause, among others, road congestion, air pollution, waste of fuel and road damage. The road that is often jammed if left unchecked will have an impact on the smooth journey and satisfaction of road users. Along with the development of information technology, this can be overcome with applications based on Geographic Information Systems and crowdsourcing, where road users can see road congestion through their mobile devices in real time. Research related to the Design of a Geographic Information System to Monitor Road Conditions Utilizing Twitter Social Media has been carried out but is limited to Twitter users[5]. To overcome the road congestion, a crowdsourcing-based application solution is needed. Based on this problem, a crowdsourcing-based application with Java and PHP languages is needed and uses a MySQL database. The advantage of this application is that it can display information on road congestion, alternative routes in Malang City to the Malang City Transportation and Traffic Police Office and road users directly at the point of congestion through their devices.